Task-oriented speech and information processing - Bhagwat, Vineet; Shirley, Sara E.; Stark, Jeffrey R. (Journal of Banking & Finance, 2024)
We examine the impact of task-oriented speech (TOS) on market participants’ ability to process new information, where TOS quantifies a more direct method of communication. Focusing on a widely publicized information event, conference calls, we show that greater TOS is associated with lower ex-post total and idiosyncratic volatility and abnormal trading volume, even after controlling for linguistic characteristics, hard versus soft information, industry effects, and ex-ante implied volatility. TOS also impacts financial analysts: forecast error, forecast dispersion and disagreement are lower during the subsequent quarter. Overall, greater use of TOS increases the ability of financial markets to efficiently evaluate new information.